2011
DOI: 10.1080/02642060903067530
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of consumers' time perceptions in a hypermarket retailer

Abstract: This study examines the effects of five antecedents on consumers' time perceptions in a hypermarket environment. Findings indicate that the actual shopping time spent in the store and planned shopping activities significantly influence consumers' shopping time perceptions, while consumers' waiting time perceptions are driven by both actual checkout waiting time and actual shopping time. The article examines time gaps, i.e. consumers' errors in time estimation, as related to store loyalty intention and finds th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Simultaneously, Governments' regulations to limit gatherings of people (including inside stores) has immediately led to long queues outside stores, not unusually with hours-long waiting times. Although previous literature has found a negative relationship between customer satisfaction and waiting time (Anić, Radas, & Miller, 2011), in the emergency context the long waiting times are not expected to negatively affect customer satisfaction with the stores; an emergency could be a situational factor affecting the perceived length of waiting time (Mowen, Licata, & McPhail, 1993). Yet, it is unknown whether the effects of situational factors persist when they are prolonged in time.…”
Section: Consumers' Buying Behavior In a Time Of Emergencymentioning
confidence: 95%
“…Simultaneously, Governments' regulations to limit gatherings of people (including inside stores) has immediately led to long queues outside stores, not unusually with hours-long waiting times. Although previous literature has found a negative relationship between customer satisfaction and waiting time (Anić, Radas, & Miller, 2011), in the emergency context the long waiting times are not expected to negatively affect customer satisfaction with the stores; an emergency could be a situational factor affecting the perceived length of waiting time (Mowen, Licata, & McPhail, 1993). Yet, it is unknown whether the effects of situational factors persist when they are prolonged in time.…”
Section: Consumers' Buying Behavior In a Time Of Emergencymentioning
confidence: 95%
“…Although such anxiety-related time distortion has been thought to be an evolutionary basis that facilitates adaptive responses to environmental stimuli (Matthews and Meck, 2014;Lake et al, 2016), in some situations, an anxious individual might not desire such time distortion. For example, previous studies have found that prolonged waiting of time can lead to anxiety (Dasu and Rao, 2009;Van Riel et al, 2012), which in turn leads to irrational decision-making behaviors (Rajamma et al, 2009;Aniae et al, 2011). Therefore, methods of reducing anxiety-related time overestimation are required.…”
Section: Introductionmentioning
confidence: 99%
“…First, the direct promotion of digital media in this study does not involve in-store shopping; thus, two factors -shopping enjoyment and in-store browsing -were excluded from the current study's research framework. In addition, because Beatty and Elizabeth Ferrell's (1998) time available construct, which originally referred to the amount of shopping time the consumer has (Ani, Radas, & Miller, 2011), did not fit the shopping scenario of this study, time pressure caused by limited-time sales promotions was instead adopted. Moreover, reviews of the literature indicated that positive and negative affects seldom coexist and that negative affect seems implicit (Carver & Scheier, 1990;Clark & Isen, 1982); thus, this study included only the positive affect.…”
Section: Research Frameworkmentioning
confidence: 99%